1997
DOI: 10.1590/s0074-02761997000500029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Molluscicidal Properties of Euphorbia splendens var. hislopii (N.E.B.) Latex: Experimental Test in an Endemic Area in the State of Minas Gerais, Brazil

Abstract: Following the positive results obtained regarding the molluscicidal properties of the latex of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 14 publications
1
8
0
2
Order By: Relevance
“…hislopii latex showed high activity in a field situation makes it a promising natural molluscicide. The result is in accord with Mendes et al (1992Mendes et al ( , 1997 and Baptista et al (1992), who have tested the latex in lentic and lotic environments, respectively, in concentrations between 5 and 12 mg/l against intermediate hosts of Schistosoma mansoni, where they also found 100% mortality.…”
Section: Discussionsupporting
confidence: 88%
“…hislopii latex showed high activity in a field situation makes it a promising natural molluscicide. The result is in accord with Mendes et al (1992Mendes et al ( , 1997 and Baptista et al (1992), who have tested the latex in lentic and lotic environments, respectively, in concentrations between 5 and 12 mg/l against intermediate hosts of Schistosoma mansoni, where they also found 100% mortality.…”
Section: Discussionsupporting
confidence: 88%
“…Other tests have demonstrated that the molluscicidal activity of the natural latex remained unchanged after storage for 124 days in a closed assay tube at room temperature and for 736 days in a closed bottle (lyophilized latex) in a refrigerator at 10-12°C (Schall et al, 1992). Field tests with the natural latex in lentic and lotic environments killed 100% of B. glabrata and B. tenagophila at concentrations of 5 and 12 ppm, respectively (Baptista et al, 1992(Baptista et al, , 1994Mendes et al, 1992Mendes et al, , 1997).…”
Section: Introductionmentioning
confidence: 99%
“…E. splendens) seems to be one of the most interesting plant molluscicides tested so far. It is active against mollusks that are intermediate hosts of Schistosoma trematodes at concentrations as low as 0.5 ppm in the laboratory and at concentrations as low as 5.0 and 12.0 ppm under "eld conditions (Vasconcellos and Schall, 1986;Mendes et al, 1997;Schall et al, 1998). Furthermore, E. milii seems to be easily grown in endemic areas, it yields a rather large amount of latex throughout the year, and its molluscicidal potency has exhibited no marked seasonal or geographic variation Schall et al, 1992).…”
Section: Introductionmentioning
confidence: 99%